2018
DOI: 10.1177/1179556518817322
|View full text |Cite
|
Sign up to set email alerts
|

Bronchopulmonary Dysplasia: An Update of Current Pharmacologic Therapies and New Approaches

Abstract: Bronchopulmonary dysplasia (BPD) remains the most prevalent long-term morbidity of surviving extremely preterm infants and is associated with significant health care utilization in infancy and beyond. Recent advances in neonatal care have resulted in improved survival of extremely low birth weight (ELBW) infants; however, the incidence of BPD has not been substantially impacted by novel interventions in this vulnerable population. The multifactorial cause of BPD requires a multi-pronged approach for prevention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 180 publications
(194 reference statements)
1
60
0
1
Order By: Relevance
“…These results make our study different from previous studies, as our study focused on the treatment of established BPD in premature infants. Ahn's study suggested that the injection of allogeneic MSCs could reduce the risk of BPD (11,23,24). It was suggested that the earliest time at whichBPD can be predicted is day 4 of life, when the peak inspiratory ventilator pressure is recorded and assisted ventilation is required (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results make our study different from previous studies, as our study focused on the treatment of established BPD in premature infants. Ahn's study suggested that the injection of allogeneic MSCs could reduce the risk of BPD (11,23,24). It was suggested that the earliest time at whichBPD can be predicted is day 4 of life, when the peak inspiratory ventilator pressure is recorded and assisted ventilation is required (25).…”
Section: Discussionmentioning
confidence: 99%
“…In the last 50 years, advances in neonatal medicine, including the discovery of neonatal steroid treatments (4,5), surfactants (6)(7)(8), gentle ventilation treatments (9,10), and effective noninvasive ventilation devices, have signi cantly improvedthe clinical outcomes inpremature newborns with BPD. However, the rates of complications and mortality are still high among infants with BPD (11).…”
Section: Introductionmentioning
confidence: 99%
“…Assessments were based on the following: (1) whether random sequences were generated and are correct; (2) whether to distribute concealment; (3) whether to study blindness of the subjects, and whether the outcome was influenced by the lack of blinding; (4) whether to blind the study results; (5) Whether the outcome measures were complete; (6) whether selective reports, loss of follow-up, or shedding cases are described.…”
Section: Document Screening Data Extraction and Quality Evaluationmentioning
confidence: 99%
“…Clinicians can effectively treat neonatal respiratory disease that is characterized by progressive dyspnea with the prophylactic application of corticosteroids. The pharmacological basis is that glucocorticoids induce newborns to produce pulmonary surfactants, thereby reducing pulmonary resistance and increasing the concentration of other drugs in the alveoli [5]. Considering that premature infants with low birth weights account for more than 50.…”
Section: Introductionmentioning
confidence: 99%
“…A chronic lung disorder of preterm birth, bronchopulmonary dysplasia (BPD) is triggered by the disturbances in physiologic lung development (Shahzad et al 2016). BPD is predominantly characterized by simplified alveolar structure, arrested lung growth, impaired vascular development, and abnormal pulmonary function (Michael et al 2018). It is documented that BPD leads to a remarkable morbidity and mortality among preterm infants (Pasha et al 2018).…”
Section: Introductionmentioning
confidence: 99%